2015
DOI: 10.1515/plc-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

Letter Visibility and the Optimal Viewing Position Effect of Isolated Connected and Un-Connected Letters in Arabic

Abstract: Th e present study provides a further exploration of the role of Arabic lett er visibility as a possible cause of the Optimal Viewing Position (OVP) eff ect. We used isolated connected and un-connected Arabic lett ers of diff erent shapes (basic, initial, medial, fi nal) placed at the center of fi xation (Experiment 1) and at various possible positions in isolated presentation (Experiment 2). In order to investigate whether performance in the visual identifi cation task is modulated by lett er type, we present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 91 publications
(112 reference statements)
0
9
0
Order By: Relevance
“…This was attributed to the complexity of Arabic letter visual representations, including letter connectedness. However, a series of experiments have also indicated that, for skilled Arabic readers, the identification of words containing semi‐connected letters is more prone to error than words containing connected letters (Ganayim, 2015; Khateb et al, 2013; Taha, Ibrahim, & Khateb, 2013). These latter findings suggest that, although semi‐connected letters might be visually simpler, ligatures facilitate word identification accuracy.…”
Section: The Arabic Language and Writing Systemmentioning
confidence: 99%
“…This was attributed to the complexity of Arabic letter visual representations, including letter connectedness. However, a series of experiments have also indicated that, for skilled Arabic readers, the identification of words containing semi‐connected letters is more prone to error than words containing connected letters (Ganayim, 2015; Khateb et al, 2013; Taha, Ibrahim, & Khateb, 2013). These latter findings suggest that, although semi‐connected letters might be visually simpler, ligatures facilitate word identification accuracy.…”
Section: The Arabic Language and Writing Systemmentioning
confidence: 99%
“…This study further indicated that skilled Arabic readers were slower at letter identification when target letters were presented in different allographic forms compared with when they were presented only in their typical isolated forms. Ganayim (2015) also found that letter recognition in Arabic is influenced by both letter type and allographic form. In this study, skilled Arabic readers had longer identification times for unconnecting letters than for connecting letters, likely due to the fact that unconnecting letters occur less frequently in this script.…”
Section: Letter Connectedness and Reading Difficulty In Arabicmentioning
confidence: 85%
“…These results were interpreted to indicate that, contrary to the idea that visual complexity causes processing difficulty during word recognition, there appeared to be processing costs for unconnected words—arguably the least visually complex of the word types that were tested. This somewhat unexpected result was attributed to the fact that the unconnecting letters that made up these words occur less frequently than connecting letters in Arabic (again, see Ganayim, 2015) and that most Arabic words contain multi-letter graphemic chunks. The same word types were also examined in a lexical decision task with both skilled and dyslexic Arabic readers (Khateb et al, 2013).…”
Section: Letter Connectedness and Reading Difficulty In Arabicmentioning
confidence: 99%
See 2 more Smart Citations